The Effect of Water Spray Systems on Thermal and Solar Performance of an ETFE Panel for Building Envelope. (2016) - Mainini, Andrea Giovanni; Speroni, Alberto; Zani, Andrea; Poli, Tiziana
Abstract: ETFE membranes are generally used in architecture for large roofing and façade systems, because of their transparency and lightness compared to glass alternatives. Multilayer ETFE panels are used to improve single membrane systems performances, reducing thermal losses, by the use of an air gap between two or more ETFE foils, generally serigraphed or surface treated to reduce solar gains. Surface temperatures and global solar radiation strongly affects mean radiant temperature (MRT), and comfort perceived by a user facing a transparent envelope as well as solar gains strongly influences primary energy use for cooling in summer conditions. In the following paper an alternative dynamic solar gains mitigation strategy is presented and applied to a double layer, non-cushions, ETFE panel for façades. We measured the effectiveness of a water spray system located in the air-gap between the parallel ETFE foils and used to reduce surface temperatures and solar access depending on different summer solar radiation values and outdoor/indoor air temperature conditions. Systems alternative with different in nozzle dimension, water spray geometry and water consumption were already tested to evaluate the best compromise between solar gains reduction and water use. The results are preliminary but we noticed that a reduction up to the 10% of the total solar gains could be achieved as well as a reduction of 10 °C of surface temperature. Comfort evaluation for a standard indoor space were already done.